Konservasi Kearifan Budaya Lokal dalam Proses Interaksi Sosial Etnis Melayu di Kabupaten Batu Bara - Ramli Nur (Islamica: Jurnal Studi Keislaman, 2016)
The article examines the local wisdoms of ethnic Malay in the district of Batu Bara as a reference for their individual and social interactions with special focus on interethnic relationships, particularly within socio-religious realm. The study finds that ethnic diversity in the district of Batu Bara is not an obstacle to create a harmonious relation in social, economic, political, and religious activities among the people. It means that the Malays in Batu Bara have virtuous interaction with other ethnicities in the region. They, for an instance, are able to build mutual trust with other ethnicities in economic activities. In addition, they are able to work hand-in-hand with other people in many areas of social aspects. It is also found that the Malays of Batu Bara treat other ethnicities as equal in terms of providing an individual his/her social stratum to be, for an example, a prominent figure of society. They also give other people from other ethnicities chance of being political elites or leaders of mass organizations. The study finds that, however, the Malays of Batu Bara tend to choose the local (indigenous) person as their leader.